Pengaruh Tayangan Indonesia Bagus NET TV terhadap Kebudayaan Siswa-Siswi MAN Baturaja Sumatera Selatan - Marini (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2021)
The rise of television programs has an impact on the audience who watch them. This influence can have a positive or negative impact depending on the type of impression itself. If a show is watched for a long enough period of time and repeatedly, it will have an impact on the audience. This study aims to determine whether there is an influence watching the Indonesian Bagus program on NET TV with the level of knowledge about culture and cultural attitudes of the students of MAN Baturaja, South Sumatra. This study uses a quantitative explanatory approach with an experimental design. The theory used is cultivation which was developed to explain the impact of watching television for heavy viewers. George Gerbner stated that for heavy viewers of television, it will essentially monopolize and include information sources. The result of this research is if a show will not affect the heavy viewers audience. However, a show can have an impact, depending on the quality of the show itself.